2004
DOI: 10.1023/b:nere.0000042218.27842.79
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Proteolytic Degradation of Bovine Brain Calcineurin by m-Calpain

Abstract: A major cause of neuronal dysfunction is due to altered Ca2+ regulation. An increase in Ca2+ influx can activate Ca2+-dependent enzymes including calpains, causing the proteolysis of its specific substrates. In the present study, calcineurin (CaN) was found to be proteolysed by a Ca2+-dependent cysteine protease, m-calpain. In the presence of Ca2+, the 60 kDa subunit (CaN A) was degraded to a 46 kDa immunoreactive fragment, whereas in the presence of Ca2+ /calmodulin (CaM) immunoreactive fragments of 48 and 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Recently, we observed higher expression of mcalpain, a Ca 2þ -activated cysteine protease in human colorectal adenocarcinomas [Lakshmikuttyamma et al, 2004c]. Furthermore, we demonstrated the in vitro proteolysis of brain CaN by m-calpain and the enhancement of its phosphatase activity after proteolysis [Lakshmikuttyamma et al, 2004a]. It may be possible that m-calpain plays a role in enhancing the expression of CaN in colon tumor.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Recently, we observed higher expression of mcalpain, a Ca 2þ -activated cysteine protease in human colorectal adenocarcinomas [Lakshmikuttyamma et al, 2004c]. Furthermore, we demonstrated the in vitro proteolysis of brain CaN by m-calpain and the enhancement of its phosphatase activity after proteolysis [Lakshmikuttyamma et al, 2004a]. It may be possible that m-calpain plays a role in enhancing the expression of CaN in colon tumor.…”
Section: Discussionmentioning
confidence: 65%
“…CaN activity was assayed using p-nitrophenylphosphate (pNPP) as a substrate [Pallen and Wang, 1983;Lakshmikuttyamma et al, 2003Lakshmikuttyamma et al, , 2004a. The reaction mixture contained 50 mM Tris-HCl, pH 7.0, 1 mM Ni 2þ , 5 mg CaM, 3.4 mM pNPP, and CaN in a total volume of 1.0 ml.…”
Section: Can Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…3, A and B, during the homogenization procedure. Previous studies have demonstrated that calpain can cleave and activate CaN A in vitro (18,20,21). When CaN A is incubated with calpain I, CaN A is truncated into a 55-to 57-kDa transient form and then further into a 43-to 49-kDa form (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…CaN A can also be activated by proteolytic cleavage of the autoinhibitory domain, resulting in a Ca 2ϩ /calmodulin-independent, active phosphatase (16,19,20). It has been reported that calpain I cleaves and activates CaN (18,21). Hence, the phosphatase activity of CaN is regulated by both Ca ϩ2 /calmodulin and calpain activation.…”
mentioning
confidence: 99%